Diversity, Evenness, and Abundance of Epiphytic Ferns in The Area Around Villa Silma, Cilember Sub-District, Bogor Regency - Siska Aprilia Kaulika; Imam Safir Alwan Nurza (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
This research aimed to find out the diversity, evenness, and distribution abundance of epiphytic ferns scattered in the area around Villa Silma, Cilember District, Bogor Regency. This research used a purposive sampling method by taking samples as the data determined by determining the characteristics of the epiphytic ferns found. Collecting data in this research exploratively by exploring all epiphytic ferns found in the area and observations on the morphology of epiphytic ferns. Data were analyzed through the diversity index using the Shannon-Wiener index, distribution of abundance using the Margalef index, and evenness index using based on the value of the Shannon-Wiener species diversity index. The research results obtained that three species of epiphytic ferns were found in the area around Villa Silma, namely Asplenium nidus L., Asplenium adiantum-nigrum L., and Pyrrosia piloselloides (L.) M.G. Price with different numbers of individuals. The diversity index of epiphytic fern is 0.7 which indicates the level of diversity in the area is low. Then, The distribution of abundance and evenness epiphytic ferns is 0.6 which indicates that there are epiphytic ferns dominant in the area and the number of individuals in each species is unevenly distributed. The most abundant fern epiphytic was found is Asplenium nidus L. with 84 individuals. This because the environment allows it to spread and grow the spores of this epiphytic fern plant properly.